ENFORCEMENT OF TAX LAW IMPLIED IN TAX AMNESTY - Claudia Permatasari Simanjuntak; Indrawati (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Tax amnesty program initiated by the Ministry of Finance through the Director General of Taxes brings huge benefits to the country’s income in the tax sector. Hence, there was a tendency that tax amnesty could potentially provide benefits for taxpayers to commit corruption, money laundering, and other violations that could harm the country. The purpose of this research to find out how the authority of the tax authorities in tax law enforcement Indonesia after the enactment of tax amnesty and knowing the supervision after the enactment of tax amnesty. This study used the type of doctrinal research by providing a systematic explanation of the legal rules governing in this case the amnesty program. The approach used in this study was the statute approach and the conceptual approach. The authority of the tax authorities in conducting tax law enforcement after the implementation of the tax amnesty program is still valid for taxpayers who commit violations such as mistakes or errors in writing the tax return as well as providing false data in the tax return. All taxpayer’s assets must be kept secret or protected by the tax authorities or the state in accordance with applicable laws and regulations. The existence of a tax amnesty program is not merely only a means of the government in increasing tax revenue, but also as a means to enforce the law in its implementation practices which are binding both in terms of the tax authorities and from the side of the taxpayer.